(3GdbhGYO GdEbJUGOjI aj EfTGA hJWhjQ GdeOf GdLOjOIs - (3EHQGgje(B, (3WdYJs ((3GdbGgQI(B:s (3OGQ GdcJGH GdMOjK(B,s, 2011)
(3JGQjN hOhGaY GfTGA GdeOf GdLOjOI(B- (3eaghe GdeOf GdLOjOI aj GWGQ SjGSI GdeLJeYGJ GdYeQGfjI GdLOjOI(B- (3GdbGYOI GdEbJUGOjI hGdfeh GdScGfj ddeOf GdLOjOI(B- (3GdMLe GdGeKd ddeOjfI GdLOjOI(B- (3Jehjd GSJKeGQGJ GdeOf GdLOjOI(B- (3GWGQ fXQj dOQGSI LOhi GfTGA GdeOf GdLOjOI(B- (3HQfGeL GfTGA GdeOf GdLOjOI aj LeghQjI eUQ GdYQHjIs
(3GdeQGLY U(B.333s
Keywords: (3GdEbJUGOs; (3GdJNWjW GdEbJUGOjs; (3GdJfejI GdEbJUGOjIs